1993
DOI: 10.4319/lo.1993.38.4.0725
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient chemistry of the water column of Lake Tanganyika

Abstract: Lake Tanganyika shows pcrmancnt thermal stratification with deep-water temperatures that have been stable over the period of observation (since 1939). The lake is anoxic below -150-m depth. In general the nutrients show Redficld behavior save in the deep waters of the northern basin where large excesses of phosphate and ammonia are prcscnt. Bacterial disproportionation of organic material probably plays an important role in producing these excesses. Inorganic dcsorption from fluvial detritus is also a possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
79
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 16 publications
(21 reference statements)
8
79
0
Order By: Relevance
“…Lake Kivu, Lake Malawi, and shallow Lake Kyoga (Table 6) were severely P deficient, while Lake George would be considered severely deficient in both N and P. Viner (1973) found rapid uptake in the dark of phosphate and ammonium added to samples of water from Lake George and concluded that both elements could control phytoplankton growth in the lake. There are no particulate analyses for Lake Tanganyika, but Edmond et al (1993) found that inorganic fixed N and phosphate were regenerated in near-Redfield proportions.…”
Section: Discussionmentioning
confidence: 99%
“…Lake Kivu, Lake Malawi, and shallow Lake Kyoga (Table 6) were severely P deficient, while Lake George would be considered severely deficient in both N and P. Viner (1973) found rapid uptake in the dark of phosphate and ammonium added to samples of water from Lake George and concluded that both elements could control phytoplankton growth in the lake. There are no particulate analyses for Lake Tanganyika, but Edmond et al (1993) found that inorganic fixed N and phosphate were regenerated in near-Redfield proportions.…”
Section: Discussionmentioning
confidence: 99%
“…1), one in the north and one in the south, each of which is over 1300 m deep. The lake is meromictic (i.e., seasonal mixing affects only the upper layers, while below 100-200 m in depth the lake water is permanently anoxic and relatively rich in nutrients) (Hecky et al 1991;Edmond et al 1993). Vertical exchange and especially upwelling driven by southeast trade winds provide the prime nutrient source to sustain primary production by internal nutrient loading .…”
mentioning
confidence: 99%
“…N limitation has been inferred from low dissolved inorganic N : P (Coulter 1977;Hecky et al 1991;Edmond et al 1993) and is indicated by blooms of N-fixing cyanobacteria following upwelling (Hecky and Kling 1981;Salonen et al 1999;Descy et al 2005). In contrast, whole-lake nutrient budgets implicate P as the ''master element'' (Hecky et al 1996), and dissolved nutrient ratios sometimes indicate P limitation (Chale 2004).…”
mentioning
confidence: 99%